Experiences of fasting during Ramadan in British Muslims: Psychological, social and health behaviours - Aaminah Latif; Syka Iqbal; Eleanor J. Bryant; Valerie E. Lesk; Barbara J. Stewart-Knox (PLoS ONE, 2025)
Ramadan is a month-long religious festival observed by Muslim worldwide, characterised by intermittent fasting. This qualitative study addressed the need to understand how fasting is experienced by Muslims residing in Western cultures, aiming to inform policies that create a more supportive environment. Practicing Muslims, both men and women, were recruited in the North of England in the United Kingdom (UK). Data were collected by individual interviews (N = 7) and focus group discussion (N = 4) and then analysed using Social Ecological Theory as a framework. Fasting was managed at the individual level through instrumental food choice and eating practices, and by adapting sleep routines. Disrupted sleep routines posed a challenge for those who had to adhere to Western working schedules, leading to perceived detriments to cognitive function and mood. The sense of belonging associated with Ramadan was seen as a motivating factor for fasting. Breaking the fast (Iftar) was marked by social activity and the availability of traditional fried foods. Participants identified the wider Western culture and environment as challenging for those who are fasting. These findings imply a need for policies that enable flexible working practices for Muslims during Ramadan.